Microscopic Insights on the Multiferroic Perovskite‐Like [CH3NH3][Co(COOH)3] Compound. Issue 2 (23rd October 2017) - Mazzuca, Lidia; Cañadillas‐Delgado, Laura; Fabelo, Oscar; Rodríguez‐Velamazán, J. Alberto; Luzón, Javier; Vallcorba, Oriol; Simonet, Virginie; Colin, Claire V.; Rodríguez‐Carvajal, Juan
Abstract: The characterization of the crystal structure, phase transitions, magnetic structure and dielectric properties has been carried out on [CH3 NH3 ][Co(COOH)3 ] (1 ) perovskite‐like metal–organic compound through variable‐temperature single‐crystal and powder neutron and X‐ray diffraction and relative permittivity measurements. The paraelectric to antiferroelectric‐like phase transition observed at around 90 K is triggered by a structural phase transition; the structural studies show a change from Pnma space group at RT (1A ) to P 21 / n space group at low temperature (1B ). This phase transition involves the occurrence of small distortions in the framework and counterions. Neutron diffraction studies have shown a magnetic order showing spontaneous magnetization below 15 K, due to the occurrence of a non‐collinear antiferromagnetic structure with a weak ferromagnetic component, mainly due to the single‐ion anisotropy of the Co II ions. Abstract : The structural and magnetic phase transitions and dielectric properties show that [CH3 NH3 ][Co(COOH)3 ] compound presents a multiferroic behaviour at zero‐field. The paraelectric to antiferroelectric‐like transition observed at around 90 K, coexists with a weak ferromagnetic signal below 15 K, which arises from a non‐collinear antiferromagnetic structure, mainly due to the single‐ion anisotropy of the Co II ions.